DISCLOSURE INDEX OF HAZARDOUS TOXIC WASTE (LB3) IN INDONESIA - Sujarweni, Wiratna; Arifah, Siti (Universitas Tidar, 2023)
This research aimed to compile a toxic hazardous materials waste (LB3) disclosure index in Indonesia, knowing the difference between unweighted and weighted LB3 disclosures in manufacturing and oil and gas companies, mineral and coal mining management (Minerba). The data used was primary, sourced from FGD and questionnaires with the sampling technique used were accidental sampling. The secondary data used was the LB3 disclosure data of manufacturing and mining companies listed on the Indonesia Stock Exchange (IDX) in 2019 using purposive sampling techniques. The index preparation method used descriptive tests and independent t-test tests to look for differences in unweighted and weighted LB3 disclosures in manufacturing and mining companies. The results of this study in the form of LB3 disclosure index as many as 21 disclosure items with their respective weights. The test results were no different but the mean value of LB3 weighted disclosure (0.2945) was higher than the mean weighted value (0.283). The difference from the unweighted and weighted index is 0.0142, the difference is very small, so statistically there is no different LB3 disclosure in manufacturing companies and miners.